A noninterventional study evaluating the effectiveness of rotigotine and levodopa combination therapy in younger versus older patients with Parkinson's disease. (13th June 2018) - Woitalla, Dirk; Dunac, Antoine; Safavi, Ali; Ceravolo, Maria-Gabriella; Gomez Esteban, Juan Carlos; Pavese, Nicola; Asgharnejad, Mahnaz; Joeres, Lars; Schuller, Jan-Christof; Chaudhuri, K. Ray
ABSTRACT: Background : PD0013 was a 6-month noninterventional study in clinical practice comparing effectiveness/tolerability of rotigotine+levodopa in younger (<70 years) vs. older (≥70 years) Parkinson's disease (PD) patients. Methods : Patients previously received levodopa for ≥6 months as monotherapy/in combination with another dopamine-agonist (DA). Primary variable: Unified PD Rating Scale (UPDRS) Part-II change from baseline to end-of-observation-period (EOP). Results : 91 younger/99 older patients started rotigotine; 68 younger/62 older patients completed the study. Most switched from levodopa+another DA. Addition of rotigotine as first DA was more common in older patients (20.2% vs.15.4%). Mean ± SD rotigotine-exposure: 6.1 ± 3.4 mg/24h younger vs. 4.9 ± 2.4 mg/24h older. Eleven patients changed levodopa dose. At EOP, improvement in mean UPDRS-II was greater in younger patients ( p  = 0.0289). UPDRS-II responder-rate (≥20% decrease in UPDRS-II score) was higher in younger patients (42.3% vs. 25.9%). Improvement across age groups was similar on PD Sleep Scale-2 and Clinical Global Impressions-Improvement Scale. Adverse drug reactions (ADRs), and discontinuations because of ADRs, were more common among older patients. There were no new safety signals. Conclusions : Despite low rotigotine doses, when added to levodopa/switched from levodopa+another DA, rotigotine led to greater improvement in UPDRS-II in younger patients (<70 years). Individual patient data revealed clinically meaningful improvements in UPDRS-II in both groups.